Improved reversible visible watermark in encrypted images by reserving room before encryption and controlled pixel modification - Jangam Deepthi; Dr.T. Venugopal (The Bioscan, 2024)
With the increasing demand for secure image sharing, reversible watermarking in encrypted images has emerged as a critical area of research. This project introduces an improved reversible visible watermarking scheme that ensures efficient embedding of visible watermarks while maintaining the integrity and recoverability of the original image. The proposed approach employs a two-step methodology: Reserving Room Before Encryption (RRBE) and Controlled Pixel Modification (CPM).The RRBE technique allocates a dedicated space for the watermark in the image before encryption, minimizing the risk of distortions caused by embedding in encrypted domains. Simultaneously, CPM fine-tunes the embedding process by modifying pixel values in a controlled manner, ensuring that the visible watermark remains clear and recognizable without degrading the visual quality of the image. The proposed scheme ensures full reversibility, allowing the original image to be recovered without loss after watermark removal.The performance of the method is evaluated using metrics such as Peak Signal-to-Noise Ratio (PSNR), Structural Similarity Index (SSIM), and embedding capacity. Results demonstrate that the proposed method achieves superior performance compared to existing techniques, offering enhanced security, visual quality, and robustness. This framework has potential applications in copyright protection, secure image transmission, and tamper detection.